2012
DOI: 10.1111/ajo.12023
|View full text |Cite
|
Sign up to set email alerts
|

A prospective longitudinal study on rotation thromboelastometry in women with uncomplicated pregnancies and postpartum

Abstract: This study provides a better knowledge about physiological changes in ROTEM measurements during pregnancy. These normative data may serve as assistance for future studies and interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 17 publications
2
37
0
Order By: Relevance
“…Previous studies of TEG in pregnancy have demonstrated increased whole blood coagulability compared with nonpregnant women [14,15] and increasing whole blood coagulability and decreasing fibrinolysis with gestational age [24,25], but limited published data looking at the combined effect of obesity and pregnancy on haemostasis. Sharma et al study [17] found the coagulation index was significantly higher in both obese mothers and nonpregnant women compared with the nonobese groups but that there were no differences between the pregnant and nonpregnant groups when matched for BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of TEG in pregnancy have demonstrated increased whole blood coagulability compared with nonpregnant women [14,15] and increasing whole blood coagulability and decreasing fibrinolysis with gestational age [24,25], but limited published data looking at the combined effect of obesity and pregnancy on haemostasis. Sharma et al study [17] found the coagulation index was significantly higher in both obese mothers and nonpregnant women compared with the nonobese groups but that there were no differences between the pregnant and nonpregnant groups when matched for BMI.…”
Section: Discussionmentioning
confidence: 99%
“…According to Rheenen-Flach et al [19], the mean INTEM (addition of ellagic acid and phospholipid to the ROTEM assay) MCF for pregnant women at 32-41 weeks gestation was 71 mm, with a standard deviation of 4 mm. Another study publishing reference ranges in pregnancy found some wider variation in the INTEM MCF (median 71, 2.5% to 97.5% 55 to 79 mm); INTEM and NATEM MCF ranges are similar [20].…”
Section: Discussionmentioning
confidence: 99%
“…Additional research is needed to determine the in vivo significance of increased ROTEM parameters in this subgroup of women. While some normative data exists for ROTEM during pregnancy [19,20,26], our study is unique in that it provides data on the effect of antifibrinolytic therapy on ROTEM values in pregnancy. The major advantage of ROTEM over standard coagulation assays is that it measures whole blood coagulation instead of coagulation in blood fractions such as platelet-poor plasma [23].…”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence that the ROTEM FIBTEM A5 assay (available within 10 min) can be used as a surrogate for Clauss fibrinogen during PPH [18,19,27,39]. It is important to recognise that this assay does not measure the same haemostatic parameter as Clauss fibrinogen, but provides similar measures of haemostatic competence [27].…”
Section: Monitoring Haemostasismentioning
confidence: 99%
“…These changes result in shorter prothrombin and activated partial thromboplastin times (PT/aPTT), sometimes below the normal laboratory range, and a large increase in thrombo-elastographic parameters such as maximum clot firmness (MCF) and maximum amplitude (MA) [17][18][19][20][21]. Natural anticoagulants such as protein S fall, contributing to the prothrombotic state [22], and there is an increase in fibrinolysis, especially in the uterus at the time of placental separation [23,24].…”
mentioning
confidence: 99%